Síndrome Pós-COVID-19 em região de fronteira: análise de fatores clínicos e sociodemográficos - Nunes, Douglas da Luz (2025)
Covid-19 has posed significant health and social challenges, including post-covid-19 syndrome (PCS), characterized by persistent symptoms following acute infection. Physical activity plays a key role in promoting health and reducing the risk of various chronic non-communicable diseases, yet its relationship with PCS remains not fully understood. Furthermore, border regions like Foz do Iguaçu present unique factors that may influence covid-19 dynamics due to high cross-border mobility and unequal access to healthcare services. This study aimed to analyze the association between PCS, physical activity levels, and sedentary behavior in individuals diagnosed with covid-19 between March 2020 and March 2023 in a tri-border city. This is a quantitative, descriptive, exploratory, and ex-post-facto study conducted with 386 participants who responded to an electronic questionnaire covering sociodemographic information, comorbidities, persistent symptoms, physical activity levels, and sedentary behavior. Statistical analysis included the chi-square test to assess associations between categorical variables, considering p < 0.05 as statistically significant. Results indicated that 40% of participants presented PCS, with a higher prevalence among women (45.2%) and individuals with comorbidities, particularly obesity, hypertension, and diabetes. Prior covid-19 vaccination was associated with a lower prevalence of PCS (p = 0.003), reinforcing the importance of immunization in mitigating persistent symptoms. No significant association was found between physical activity levels and PCS (p = 0.648) or between sedentary behavior and PCS (p = 0.678), suggesting that these factors alone may not be decisive in PCS development. However, existing literature highlights the benefits of physical activity in functional recovery and symptom reduction. This study underscores the need for public policies focused on PCS rehabilitation, including multidisciplinary strategies for monitoring and managing the condition. Additionally, further research is needed to explore the relationship between physical activity, exercise intensity, and PCS progression over time.